STRATEGI WAKIL KEPALA SEKOLAH BIDANG KESISWAAN DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SMK MAHARDIKA SINGKEP - Toni; Nurlaila Susanti; Andrias Fabaitya (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2025)
A common problem in school environments is the lack of discipline ofstudents in obeying the rules that apply in the school. Therefore, efforts need to bemade by the school in dealing with the problem of disciplinary violations committedby students at school. This study aims to determine: 1) The strategy of the viceprincipal for student affairs in improving student discipline at SMK MahardikaSingkep, 2) Inhibiting factors for the vice principal for student affairs in improvingstudent discipline at SMK Mahardika Singkep. The method used in this study is aqualitative method. The data sources for this study are primary data and secondarydata. Data collection techniques used in this study are observation, interviews anddocumentation. The data analysis techniques used are data reduction, datapresentation, conclusions and verification. The results of the research on thestrategies of the vice principal for student affairs in improving student discipline atSMK Mahardika Singkep include: a) Socializing students about school regulations,b) giving reprimands and advice to students who are not disciplined, c) givingsanctions to students who are not disciplined, d) supervising student discipline. (2)Inhibiting factors for the vice principal for student affairs in improving studentdiscipline at SMK Mahardika Singkep include: a) lack of student self-awareness b)environmental influences.